Penguatan Pemahaman Masyarakat Mengenai Kepastian Hukum dalam Pembagian Hak Waris atas Tanah di Kelurahan Kebun Kenanga - Delty Maiesa Anggraeny; Zacky Antony; Hikmah Aisyah; Mutiara Utari Irma Dayani; Inka Ayu Afriana; Indah Juniarti; Mulya Mulya; Ahmad Johanda; Dewi Puspitasari; Teguh Pramuctio; Milhan Ali Da’i Nasution; Taufiqur Rahman; Farhan Hanif; Rasyidiatul Umami; Herlian Fernandes (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
Legal certainty in the distribution of inheritance rights over land is an important aspect in preventing ownership disputes within society. Based on observations conducted in Kebun Kenanga Village, several issues were identified, including land ownership conflicts between parties holding official land certificates issued by the National Land Agency (BPN) and parties claiming ownership based on grants (hibah). In addition, cases of overlapping land documents and limited public understanding regarding the legal procedures for transferring land rights through inheritance and grants were also found. On the other hand, the community possesses valuable assets, including support from village officials, community leaders, and active public participation, which can be utilized to enhance legal awareness. This community service activity aimed to improve public understanding of the importance of legal certainty in the distribution of inheritance rights over land. The method used was Asset Based Community Development (ABCD) through the stages of discovery, dream, design, and destiny. The program was implemented through legal counseling, discussions, and question-and-answer sessions with community members. The results showed an increase in public understanding regarding inheritance law, the legal status of grants, the evidentiary strength of land certificates, and the importance of land registration as a form of legal protection. The Societal Impact Index (SII) indicated a high category with an average score of 4.6. This activity generated positive social impacts by increasing legal awareness, reducing the potential for land disputes, and encouraging orderly land administration practices within the Kebun Kenanga community.